The role of Non Governmental Organisations (NGOs)in natural heritage conservation: a case study of Ulu Muda Forest Reserve - Chuah , Chiew Yen; Ong , Kee Shin; Chan , Ngai Weng (Environmental Management Society, Malaysia, 2011)
The Ulu Muda Forest Reserve plays an important role as a water catchment area that supplies fresh water for domestic, industrial and agriculture sectors of the northern part of Peninsular Malaysiafor the states of Kedah, Penang and Perlis. The largest rice growing state Kedah, it also known as "Rice Bowl" of Malaysia, is heavily dependant on the fresh water sourced from Ulu Muda Forest Reserve. Other than supply of fresh water,the forest is also rich is biodiversity, and has many rare species such as the globally-threatened plain-pouch hornbill, elephants, tapir and dipterocarp species (high economic value timber).There also the number of saltlicks which have high tourism related potentials.In 2002,the state government of Kedah granted in principle a timber harvesting project 122,798 ha of forests to be logged by the privatesector via helicopter-logging method. However , the project was stalled after strong lobbying from the friend of Ulu Muda (FoUM), a coalition of non-governmental organizations (NGOs)and community based organizations,as well as well rejection of detailed environmental Impact Assesment by the Department of Environmental, which is under the purview of the Ministry of Natural Resources and the Environment. In 2008,FoUM II was reintiated when the logging project was again being proposed by the current Kedah state government.FoUM II has made their stand strong and firm and has come out with several suggestions to prevent the forest from being logged. This article examines the importance and treats of Ulu Muda Foreat Reserve, the role of FoUM in protecting Ulu Muda Forest Reserve and recommendations to protect Ulu Muda Forest Reserve (UMFR).